2019
DOI: 10.1007/s10681-019-2404-7
|View full text |Cite
|
Sign up to set email alerts
|

Modern wheat semi-dwarfs root deep on demand: response of rooting depth to drought in a set of Swiss era wheats covering 100 years of breeding

Abstract: Breeding for enhanced rooting depth and root biomass in deeper soil layers is a promising strategy to adapt wheat (Triticum aestivum L.) plants to drought periods. We evaluated (1) the extent of indirect selection of root traits during the last century of wheat breeding and (2) how it affected the variety performance under well-watered conditions compared to gradually developing drought stress. Fourteen bread wheat genotypes covering 100 years of Swiss wheat breeding were grown in 1.6 m tall columns in the gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 44 publications
9
47
2
1
Order By: Relevance
“…The modification of rooting patterns (distribution, morphology, density) in response to changes in soil water status has been described for wheat. Root dry weight, length and density of wheat changed its vertical distribution in response to both early and late water stress [48][49][50], and a similar phenomenon of root compensation was observed [51] in a study with adult wheat plants grown in soils with contrasting humidity at the top and bottom soil layers. When the top layer was dry and the bottom one was wet, the plants had a larger root system than when grown in fully wet soils, which indicated enhanced root growth in the wet soil part when it was stimulated by water stress in another soil area.…”
Section: Low Water Availability Causes Changes In Root System Architementioning
confidence: 54%
“…The modification of rooting patterns (distribution, morphology, density) in response to changes in soil water status has been described for wheat. Root dry weight, length and density of wheat changed its vertical distribution in response to both early and late water stress [48][49][50], and a similar phenomenon of root compensation was observed [51] in a study with adult wheat plants grown in soils with contrasting humidity at the top and bottom soil layers. When the top layer was dry and the bottom one was wet, the plants had a larger root system than when grown in fully wet soils, which indicated enhanced root growth in the wet soil part when it was stimulated by water stress in another soil area.…”
Section: Low Water Availability Causes Changes In Root System Architementioning
confidence: 54%
“…Four wheat (Triticum aestivum L.) cultivars from the Swiss wheat breeding program (Fossati and Brabant, 2003;Friedli et al, 2019) with different breeding ages were selected: Mont-Calme 268 (introduced in 1926), Probus (1948), Zinal (2003 and CH Claro (2007). Generally, more recent cultivars of this program on average have more shallow roots and lower root biomass under well-watered conditions compared to the older cultivars (Friedli et al, 2019). CH Claro was selected as a modern variety with relatively deep rooting.…”
Section: Wheat Cultivars and Growth Conditionsmentioning
confidence: 99%
“…One way to evaluate the effect of breeder's selection on root characteristics and subsoil carbon cycling is to compare old and new varieties of the same breeding programme. For the Swiss wheat breeding programmes, the selection process reduced the mass and depth of roots under well-watered conditions but modern genotypes enhanced root allocation to deep soil layers under drought (Friedli et al, 2019). The negative trend of rooting depth was also present in other breeding programmes (Aziz et al, 2017), but has not been observed consistently (Cholick et al, 1977;Feil, 1992;Lupton et al, 1974).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations